Successful Treatment of Carbamazepine-Induced Toxic Epidermal Necrolysis With Clinical Gastrointestinal Involvement: A Case Report - Le Quynh Chi; Nguyen Thi Van Anh; Nguyen Ngoc Quynh Le; Nguyen Thi Thu Ha; Hoang Minh Tien; Tran Minh Dien (Frontiers Media S.A., 2022)
BackgroundStevens-Johnson syndrome/toxic epidermal necrolysis (SJS/TEN) is a rare and life-threatening disease of the skin and mucosal surfaces. Although gastrointestinal manifestations in adults are potential prognostic factors for disease severity, there are limited data on such cases and their standard management in the pediatric population.Case PresentationWe herein report the case of an 8-year-old girl with a 1-year history of epilepsy, who presented with bilateral conjunctivitis and progressively widespread bullous, and pruritic eruption based on erythematous skin after administration of carbamazepine. A diagnosis of carbamazepine-induced TEN was made, and the drug was immediately discontinued. The result of genetic screening showed that the patient was positive for the HLA-B*15:02 allele. Then, her condition got worse by developing gastrointestinal involvement, including hematemesis and severe watery bloody diarrhea. A combination of the intravenous immunoglobulin and the appropriate dose of systemic steroids have contributed to a favorable outcome in this case. Multidisciplinary care of mucocutaneous involvement, supplemental nutrition, and fluid replacement was also critically warranted. This report aims to contribute to the current literature on TEN-related gastrointestinal manifestations in pediatrics and highlights the need for further investigations in determining the optimal treatment in such cases.ConclusionIn conclusion, we reported the successful treatment of TEN-related gastrointestinal manifestations in a pediatric patient, which should be critically considered in patients with SJS/TEN. Since it may significantly contribute to the poor prognosis of the illness, further investigations in determining standard management in such cases are necessary.